517 Regulatory T cell functional identity is sustained by a glucose:lactate axis that is exploited in the tumor microenvironment. (9th November 2020) - Watson, McLane; Vignali, Paolo; Mullet, Steven; Overacre-Delgoffe, Abigail; Peralta, Ronal; Grebinoski, Stephanie; Menk, Ashley; Rittenhouse, Natalie; DePeaux, Kristin; Whetstone, Ryan; Vignali, Dario; Hand, Timothy; et al.
Abstract : Background: Regulatory T (Treg) cells are vital for preventing autoimmunity but are a major barrier to robust cancer immunity as the tumor microenvironment (TME) recruits and promotes their function. The deregulated cellular metabolism of tumor cells leads to a metabolite-depleted, hypoxic, and acidic TME. While the TME impairs the effector function of highly glycolytic tumor infiltrating CD8 T cells, Treg cell suppressive function is maintained. Further, studies of in vitro induced and ex vivo Treg cells reveal a distinct metabolic profile compared to effector T cells. Thus, it may be that the altered metabolic landscape of the TME and the increased activity of intratumoral Treg cells are linked. Methods: Flow cytometry, isotopic flux analysis, Foxp3 driven Cre-lox, glucose tracers, Seahorse extracellular flux analysis, RNA sequencing. Results: Here we show Treg cells display heterogeneity in terms of their glucose metabolism and can engage an alternative metabolic pathway to maintain their high suppressive function and proliferation within the TME and other tissues. Tissue derived Treg cells (both at the steady state and under inflammatory conditions) show broad heterogeneity in their ability to take up glucose. However, glucose uptake correlates with poorer suppressive function and long-term functional stability, and culture of Treg cells in high glucose conditions decreased suppressive function. Treg cells under low glucose conditions upregulate genes associated with the uptake and metabolism of the glycolytic end-product lactic acid. Treg cells withstand high lactate conditions, and lactate treatment prevents the destabilizing effects of high glucose culture. Treg cells utilize lactate within the TCA cycle and generate phosphoenolpyruvate (PEP), a critical intermediate that can fuel intratumoral Treg cell proliferation in vivo. Using mice with a Treg cell-restricted deletion of lactate transporter Slc16a1 (MCT1) we show MCT1 is dispensable for peripheral Treg cell function but required intratumorally, resulting in slowed tumor growth and prolonged survival. Conclusions: These data support a model in which Treg cells are metabolically flexible such that they can utilize 'alternative' metabolites present in the TME to maintain their suppressive identity. Further, our studies support the notion that tumors avoid immune destruction not only by depriving effector T cells of essential nutrients, but also by metabolically supporting regulatory T cells.